2020
DOI: 10.3390/nu12113366
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in Cancer Therapy in the Elderly—An Epigenetic Connection?

Abstract: The continuous increase in life expectancy results in a steady increase of cancer risk, which consequently increases the population of older adults with cancer. Older adults have their age-related nutritional needs and often suffer from comorbidities that may affect cancer therapy. They frequently are malnourished and present advanced-stage cancer. Therefore, this group of patients requires a special multidisciplinary approach to optimize their therapy and increase quality of life impaired by aging, cancer, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 106 publications
1
10
0
Order By: Relevance
“…They reported a need for nutrition-related guidelines and correct medical knowledge to better care for their patients at home. The finding regarding nutrition echoes a previous study that found nutrition to be a major concern of older patients with cancer because of physical function decline, comorbidities, and treatment-related side effects such as vomiting, mucositis, and nausea (Blasiak et al, 2020). Older patients with cancer who are malnourished face an up to 1.87 times higher risk of all-cause mortality (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…They reported a need for nutrition-related guidelines and correct medical knowledge to better care for their patients at home. The finding regarding nutrition echoes a previous study that found nutrition to be a major concern of older patients with cancer because of physical function decline, comorbidities, and treatment-related side effects such as vomiting, mucositis, and nausea (Blasiak et al, 2020). Older patients with cancer who are malnourished face an up to 1.87 times higher risk of all-cause mortality (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…Malnutrition due to protein energy deficiency is the most common nutritional disorder in the elderly (24). With age, the need for vitamins such as protein, calcium, vitamin D, B12 and folate increases and the need for calories decreases (25).…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition is another key indicator of poor clinical outcomes for people with cancer [ 38 ] which can lead to a multitude of problems including decreasing efficacy of cancer therapy and reduction in quality of life [ 39 ]. A recent systematic review and meta-analysis on the subject [ 40 ] identified 42 studies which found that decreased food intake was associated with increased mortality from cancer treatment (both surgery and other treatments).…”
Section: Challenges and Potential Solutionsmentioning
confidence: 99%